Apoptosis Induction of SKOV-3 Ovarian Cancer Cells from Pacing Rhizome (Costus speciosus) Through the Modulation of BAX and P53 Genes Expression - Hidayah, Alifia Brilliani; Ashfannada, Nuqya; Khasanah, Aisyah Nur; Annisa, Siti Nur; Tiffany, Ghea Rachella; Murwanti, Retno (Indonesian Journal of Cancer Chemoprevention, 2023)
Costus speciosus or Pacing has been investigated to have cytotoxic effect on several human cancer cells. Current was conducted to determine the cytotoxic activity of ethanol extract of the Pacing rhizome (EP) on SKOV-3 ovarian cancer cells, to investigate EP’s effect on BAX and p53 expression, and predict the inhibition activity on intrinsic pathway. EP were extracted using maceration method with 70% ethanol. The cytotoxic effect was performed using MTT Assay with various concentrations (375 μg/mL, 250 μg/mL, 62.5 μg/mL, 31.25 μg/mL, and 7.8125 μg/mL). The ability of EP to induce apoptosis in SKOV-3 cells was measured using flow cytometry. The BAX and p53 gene expressions on SKOV-3 cells were detected with RT-qPCR after treatment of EP with concentrations of ¼ IC50, ½ IC50, and IC50. The ability of diosgenin to interact with BAX and p53 can be seen from the interaction with the MCL-1 protein and was predicted with molecular docking. The results showed that IC50 of cytotoxic activity was 69.143 μg/mL. EP could induce apoptosis on SKOV-3 cells and can induce BAX and p53 protein expressions. The docking results show that diosgenin has the potential to act as an antagonist for the MCL-1 protein, it can increase apoptosis.Keywords: apoptotic, Costus speciosus extract, SKOV-3, p53, BAX.